2015
DOI: 10.2214/ajr.14.14022
|View full text |Cite
|
Sign up to set email alerts
|

Upright Biplanar Slot Scanning in Pediatric Orthopedics: Applications, Advantages, and Artifacts

Abstract: Upright biplanar slot scanners acquire high-resolution radiographs simultaneously in two orthogonal planes with reduced radiation dose. Other advantages include a more physiologic weightbearing imaging position, improved Cobb angle measurements, and 3D modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…However, no studies have actually examined the agreement between EOS and standard X-ray systems. In contrast to Hull's suggestion [24] , the results of the present study proved that the effect of geometrical magnification on Cobb angle measurement is insignificant. The difference in the Cobb angle measurement between imaging methods could be regarded as measurement variability rather than real error.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, no studies have actually examined the agreement between EOS and standard X-ray systems. In contrast to Hull's suggestion [24] , the results of the present study proved that the effect of geometrical magnification on Cobb angle measurement is insignificant. The difference in the Cobb angle measurement between imaging methods could be regarded as measurement variability rather than real error.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have compared the performance of EOS with CT in the measurement of scoliotic curves, and most studies reported an excellent agreement between EOS and CT in measuring Cobb angle and confirmed EOS to be a reliable and accurate imaging acquisition method for scoliosis examination [22] , [23] . It is suggested that the biplanar X-ray sources and detectors of EOS system translate simultaneously along superoinferior direction; thus, the images produced do not have geometrical magnification, contrary to conventional projection imaging systems [24] . However, no studies have actually examined the agreement between EOS and standard X-ray systems.…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved through a number of methods: viz. reducing the number of radiographs to as few as possible [ 54 ], reducing the exposed area [ 9 ] and using the optimal radiographic technique.…”
Section: Radiographymentioning
confidence: 99%
“…EOS ® has been in clinical use since 2000. It reduces radiation exposure by approximately 6 times that of conventional radiography [ 54 , 60 , 63 , 65 ]. Recently, as a result of technical advances, the microdose protocol was developed further reducing the radiation dose to patients.…”
Section: Eos ®mentioning
confidence: 99%
“…3) and increased risk of motion artifacts, especially in pediatric patients, due to a slow image acquisition process. 21 However, given that EOS appears to be equivalent to radiography for spine, hip, and chest imaging, 13,14 and putatively shunt This study has several limitations. It is retrospective and included only patients with shunted hydrocephalus due to Chiari type II malformations.…”
Section: Discussionmentioning
confidence: 90%